Stemona fimbritepala (Stemonaceae), a new species from northern Laos - Rakarcha, Sarayut; Pongamornkul, Wittaya; Thammarong, Woranart; Maknoi, Charun; Souvannakhoummane, Keooudone (Thai Forest Bulletin (Botany), 2020)
Stemona fimbritepala (Stemonaceae), a new species from northern Laos, is described and illustrated. It is morphologically similar to S. hirtella and S. kerrii but clearly differs in longer peduncle, longer tepals, longer petaloid outgrowth of the connective and fimbriate margin of inner tepals. A detailed description, distribution, ecology, etymology, preliminary conservation status and photographs of this species are provided. A key to discriminate between the three hairy species is presented.